2018
DOI: 10.1080/14686996.2018.1500851
|View full text |Cite
|
Sign up to set email alerts
|

Thickness-dependent thermoelectric power factor of polymer-functionalized semiconducting carbon nanotube thin films

Abstract: The effects of polymer structures on the thermoelectric properties of polymer-wrapped semiconducting carbon nanotubes have yet to be clarified for elucidating intrinsic transport properties. We systematically investigate thickness dependence of thermoelectric transport in thin films containing networks of conjugated polymer-wrapped semiconducting carbon nanotubes. Well-controlled doping experiments suggest that the doping homogeneity and then in-plane electrical conductivity significantly depend on film thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…9,235,252,253 Nonoguchi et al demonstrated that the plasmon resonance of free charge carriers in the infrared can also be used to systematically track relative carrier density in s-SWCNTs (Figure 21c). 254 While most molecular doping strategies do not modify the Fermi level strongly enough to quench the relatively high-energy excitonic transitions of m-SWCNTs, 255 the plasmon resonance intensity can report on systematic changes to the carrier density in m-SWCNTs. 256 However, electrostatic gating has been shown to be effective in modulating the Fermi level to a large enough degree to quench m-SWCNT excitonic transitions (Figure 21d,e), and the doping-induced tuning of the Fermi level increases the conductivity for both sand m-SWCNTs, as shown in Figure 21f,g for electrostatic doping of m-SWCNTs.…”
Section: Carbon Nanomaterialsmentioning
confidence: 99%
See 3 more Smart Citations
“…9,235,252,253 Nonoguchi et al demonstrated that the plasmon resonance of free charge carriers in the infrared can also be used to systematically track relative carrier density in s-SWCNTs (Figure 21c). 254 While most molecular doping strategies do not modify the Fermi level strongly enough to quench the relatively high-energy excitonic transitions of m-SWCNTs, 255 the plasmon resonance intensity can report on systematic changes to the carrier density in m-SWCNTs. 256 However, electrostatic gating has been shown to be effective in modulating the Fermi level to a large enough degree to quench m-SWCNT excitonic transitions (Figure 21d,e), and the doping-induced tuning of the Fermi level increases the conductivity for both sand m-SWCNTs, as shown in Figure 21f,g for electrostatic doping of m-SWCNTs.…”
Section: Carbon Nanomaterialsmentioning
confidence: 99%
“…200 nm thick films. 254 Doping also appears to lower the thermal conductivity, 9,252 although further studies are needed to determine the precise mechanism at play. With respect to stability, s-SWCNT networks tend to be less stable to environmental degradation of n-type conductivity than their mixed and metallic counterparts.…”
Section: Carbon Nanomaterialsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 7 ] Among these candidates, randomly stacked CNT films demonstrate remarkable properties. A large Seebeck coefficient over 200 μV K −1 has been reported in enriched semiconducting CNT films, [ 8–10 ] and a larger value of 2500 μV K −1 has been well theorized in individual semiconducting CNTs with small diameters. [ 11 ] Simultaneously, CNT film‐based materials exhibit excellent broadband photoabsorption characteristics, [ 12 ] flexibility, [ 13 ] mechanical strength, [ 14 ] and corrosion resistance, [ 15 ] potentially leading to promising PTE photomonitoring applications.…”
Section: Introductionmentioning
confidence: 99%